MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI GERAK RINGAN DENGAN PENDEKATAN ILMIAH BERBANTUAN PRODUK SEDERHANA - Uyuni, Qurrotul; Af’idah, Noer (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
This research aims to determine the optimization of students' learning motivation in rectilinear motion material through a scientific approach with the help of simple product. This research began with problems found in one of the junior high schools in Jombang, which had a low level of learning motivation. This research is quantitative research with a one shot case study, namely giving a posttest after students have been given treatment. The subjects of this research were 24 students in 8th grade of junior high school. The data sources in this research were teacher and students. Data from teacher is in the form of observations of learning implementation using a scientific approach. Then the data from students is in the form of posttest results, which are given after learning has been carried out using a scientific approach. The implementation of learning is assessed based on steps from a scientific approach. After obtaining implementation and posttest observation data, the data is then presented as a percentage so that the criteria are known. The results of this research indicate an increase in the learning motivation of 8th grade of junior high school students after implementing science learning with a scientific approach. This is shown in the posttest results of students with an average of 82 and the results of implementing scientific learning with an average of 92.5%. Thus, it can be seen that one way to raise students' learning motivation in science subjects, especially rectilinear movement material, is by using a scientific approach.